2014
DOI: 10.3892/ol.2014.1810
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α-induced a disintegrin and metalloprotease 10 increases apoptosis resistance in prostate cancer cells

Abstract: In developed countries, prostate cancer (PCa) is the second most frequently diagnosed type of cancer and the third most common cause of cancer-related mortality in males. Compared with western countries, the morbidity rate of PCa in China is markedly lower, however, it is rising annually. The etiology of PCa is unclear, therefore, to investigate how a disintegrin and metalloprotease 10 (ADAM10) functions in PCa, ADAM10 mRNA and protein levels induced by tumor necrosis factor (TNF)-α were identified using polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Prostate cancer (PCa) continues to plague males worldwide, ranking as a leading contributor of male death particularly in developed countries [1,2]. In China, PCa has exhibited a progressively increasing incidence and mortality rate, with a relatively higher incidence identified in urban regions and greater mortality in rural areas [3].…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) continues to plague males worldwide, ranking as a leading contributor of male death particularly in developed countries [1,2]. In China, PCa has exhibited a progressively increasing incidence and mortality rate, with a relatively higher incidence identified in urban regions and greater mortality in rural areas [3].…”
Section: Introductionmentioning
confidence: 99%
“…17 Latest reports have shown that ADAM10 siRNA-based gene therapy can be potentially utilized for treatment of different tumors, including prostate cancer. 18…”
Section: Introductionmentioning
confidence: 99%
“…To date, increasing evidence has demonstrated that ADAM10 affects the production of the inflammatory cytokines IL-6 and IL-1β in macrophages and thus, is implicated in the process of leukocyte migration and in the promotion of pro-inflammatory activity [ 18 - 20 ]. Some studies have revealed that ADAM10 inhibitors performed beneficial functions, such as increasing apoptosis resistance or suppressing the inflammatory immune response, in several cell models [ 21 - 23 ]. This evidence suggests that ADAM10 may play a vital role in the pathogenesis of directly inflammatory-related diseases, such as sepsis.…”
Section: Introductionmentioning
confidence: 99%